Penerapan Metode Finite State Machine Pada Game Pembelajaran Matematika - Antonius Fernando; Guntoro Guntoro*; Loneli Costaner; Mariza Devega; Lisnawita Lisnawita (Universitas Lancang Kuning, 2023)
Mathematics is a compulsory field of study that is learned from elementary school, junior high school, high school, and college. A very important lesson, can help every citizen in transactions in selling an item, because it can calculate the amount of income and expenses in a business and various other examples related to mathematics lessons. In learning mathematics, students experience problems in understanding mathematical material. The problem faced by students is the lack of understanding of students in learning mathematics because students are used to finding answers on the internet. In overcoming the problems experienced by students, teachers try to improve understanding of mathematics learning by teaching slowly so that students can understand mathematics learning. When the teacher finished explaining, some students did not understand and asked the teacher to explain again from the beginning. This learning game was made to increase the interest in learning for vocational school children not to be bored in learning mathematics, because most students are not interested in learning mathematics because the material is difficult to reach and makes it easier for teachers to repeat the material presented by the teacher. In this mathematics application, a multimedia-based mobile application will be created. This math application supports multimedia video, sound, image, text and also text. This study aims to make the application of the Finite State Machine Method in Mathematics Learning Games for Elementary School Children. Methods of collecting data by browsing the internet, studying books, journals. FSM as AI (Artificial Intelligence). With this game, it is hoped that it can increase knowledge and facilitate the process of learning Mathematics.The result of this application can run well in accordance with blackbox testing and the application of the fiite state machine method can also be applied in this application according to the finite state machine method testing.